Answer:
4 is the correct answer of the question
Hello :
<span>If f(x)=x/2-2 and g(x)=2x^2+x-3, find (f+g)(x)
</span>(f+g)(x)= f(x) +g(x) = x/2-2 +2x²+x-3 = x/2 +2x²+x-5
(f+g)(x)= (x+4x²-2x-10) /2
(f+g)(x)= (4x²+3x-10)/2 = 2x²+3/2 x -5
Answer: 7
Step-by-step explanation:
Answer:
Step-by-step explanation:Given Equation of line has slope m=-3/2
So the line passing through (4,6) has the same slope because both are parallel
From slope intercept form we have
y-y1=m(x-x1)
y-6=-3/2(x-4)
y-6=-3/2x +3/2(4)
y=-3/2x+12
2y=-3x+24